Resistance of ten bean genotypes to Acanthoscelides obtectus in laboratory - Souza, Lindaurea Alves de (2014)
Research work was carried out under laboratory conditions, at the "Centro de Energia Nuclear na Agricultura" (CENA/USP) at Piracicaba, SP, Brazil, with the objective of determining different levels of resistance of ten genotypes of beans (Phaseolus vulgaris L.) to the weevil Acanthoscelides obtectus. A round wooden tray (1 m diameter, 12cm raised edge) covered with a very thin cloth ('voile') was used. Forty samples of dry beans (ten genotypes and four replications) were placed on the tray and 1000 weevils released in the center of the tray so that they could have their choice of beans. After 30 days the samples were transferred to appropriate flasks and were all kept under to same conditions. After the second generation the number of holes/grain of each genotype was counted and the comparative resistance of these genotypes was studied. It was conclued that genotypes Rosinha G-2 and Goiano Precoce were highly susceptible and Piratã-2, Aroana, Moruna, Regente, SP-7052, Carioca, Jalo and Tayhu were susceptible.